Integral foam molding - A new process for foamed magnesium castings - Hirschmann, Markus; Körner, Carolin; Singer, Robert (Materials Science Forum, 2007)
Integral foam molding (IFM) is an economical near net-shape technology to produce monolithic castings with solid skin, foamed core and continuous density transition between skin and core. It was developed for polymers in the 1960s. But it took about ten years to optimize the molding technique and the quality of the polymer integral foam parts to a marketable stage. Meanwhile, polymer integral foam parts are established in a lot of commercial applications. The situation is completely different for metals. The first attempts to produce metal integral foam parts were made only a few years ago. A cost effective injection molding technique for magnesium integral foam was developed at the WTM-Institute in Erlangen, Germany. The low-cost production in combination with the integral foam properties low density, high weight specific bending stiffness and remarkable damping capacity is very promising. At the beginning we produced only parts with simple shape, for example plates. But if we think about commercial applications, more complex parts with a three-dimensional shape are required. The focus of this paper is on new developments concerning the production of magnesium integral foam parts with complex shape like a casing cover or a door handle.
Keywords: integral foam; integral foam molding; magnesium; injection molding; casting